(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The first chapter discusses many discourses on women’s past as contemporary women in India and offers an outline of women as topics of literature. In this segment, I have attempted to locate ’females’ in national and regional history, stressing the condition of women who reside in flung and poor places. I also sought to stress in this chapter that women’s role is a social framework and defines their interaction with others. In this chapter I have tried to explore the prevalent social structures through different examples, especially through established customs.